AESTHETICS OF JOURNALISTIC PHOTOGRAPHY BY WAHYU ADJI FEBRIANTO IN INSTAGRAM RADAR KEDIRI MAY – JUNE 2025 EDITION - syah, naziah; Adhytia, Rizkyhimawan; Suparti, Suparti (Arty: Jurnal Seni Rupa, 2025)
This research on photography focuses its study on the works of Wahyu Adji Febrianto collected in online news portals with the aim of describing the types of photography and aesthetic values in Wahyu Adji Febrianto's photographic works. This research is a qualitative descriptive study with data collection techniques used are documentation, bibliography, and triangulation techniques. The results of the study show that all of Adji's photographic works have or contain elements, principles, and principles of art so that they have aesthetic value in them. The types of journalistic photography that are pursued and almost always present in every news photo coverage by Wahyu Adji Febrianto are spot photography, people in the news, and sports. The aesthetic value of Adji's journalistic photography leads to the application of elements of art, principles of art, and principles of art. For the elements of art, there are elements of line, elements of color, and elements of space. For the principles or basics of art, there are the principles of contrast and the principle of rhythm. Meanwhile, for the principles of art, the photojournalist named Adji successfully applies four principles, namely the principle of unity, balance, proportion, and the principle of simplicity. The value of beauty adds to the attraction because in general journalistic photos always prioritize speed in covering news and photos.